2020
DOI: 10.18632/aging.102687
|View full text |Cite
|
Sign up to set email alerts
|

Development of prognostic index based on autophagy-related genes analysis in breast cancer

Abstract: Background: Autophagy is a self-digesting process that can satisfy the metabolic needs of cells, and is closely related to development of cancer. However, the effect of autophagy-related genes (ARGs) on the prognosis of breast cancer remains unclear. Results: We first found that 27 ARGs were significantly associated with overall survival in breast cancer. The prognosis-related ARGs signature established using the Cox regression model consists of 12 ARGs that can be divided patients into high-risk and low-risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 19 publications
0
36
2
Order By: Relevance
“…Our ROC analysis showed that the AUC was 0.842 for 3-year OS and 0.808 for 5-year OS, higher than the AUC values reported in previous models (Lin et al, 2020;Xie et al, 2019), thus indicating that our model had better predictive ability.…”
Section: Discussioncontrasting
confidence: 75%
“…Our ROC analysis showed that the AUC was 0.842 for 3-year OS and 0.808 for 5-year OS, higher than the AUC values reported in previous models (Lin et al, 2020;Xie et al, 2019), thus indicating that our model had better predictive ability.…”
Section: Discussioncontrasting
confidence: 75%
“…Recently, numerous studies have focused on certain characteristics, such as autophagy and metabolic reprogramming, to identify gene signatures that are able to predict the mortality risk of cancer (Wan et al, 2019;Lin et al, 2020;Liu et al, 2020). In this study, we identified four RBP-related genes that were able to predict the OS of CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Gu Y et al [26] mentioned that eight AGs, BCL2, BIRC5, EIF4EBP1, ERO1L, FOS, GAPDH, ITPR1, and VEGFA, were ought to be designated as prognostic markers for autophagy-associated BC. Lin QG et al [27] initially found that 27 ARGs (autophagy-related genes) were evidently associated with overall survival rate of BC. The prognostic-related ARGs signature established by the Cox regression consisted of 12 ARGs with a 5-year survival rate AUC 0.742.…”
Section: Discussionmentioning
confidence: 99%